Polyvinyl chloride plastic material and preparation method thereof

By introducing multiple collaborative protection systems of photoresponsive nanoparticles as cores and shells in polyvinyl chloride materials, halide ion carrier mesoporous materials and cerium-based metal organic framework materials, the polyvinyl chloride materials are solved in the marine environment. The problems of photoaging and microplastic pollution achieve high-efficiency light stability and degradation inhibition of materials, extend the service life and reduce the production of microplastics.

CN119220030AInactive Publication Date: 2024-12-31ANGREEN DONGGUAN NEW MATERIALS TECH

Patent Information

Application Number
CN202411507848.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Polyvinyl chloride materials are prone to photoaging in marine environments, resulting in microplastic pollution, resulting in reduced service life and marine ecological pollution.

Method used

A polyvinyl chloride plastic material is designed, containing photoresponsive nanoparticles as cores and shells, halogen ion carrier-type mesoporous materials and cerium-based metal organic framework materials. Through multiple collaborative protection systems, it includes photoresponsive nanoparticles. UV light absorption, halogen ion carrier mesoporous materials regulate halogen ion release and cerium-based metal organic framework materials capture free radicals, combine layered barrier materials to build a physical protective barrier, and form a collaborative protection network.

Benefits of technology

It significantly improves the light stability of the material, reduces the degradation rate, reduces the production of microplastics, extends the service life, and effectively prevents the erosion of the material by the seawater environment, significantly improving water resistance and oxygen resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220030A_ABST
    Figure CN119220030A_ABST
Patent Text Reader

Abstract

The invention discloses a polyvinyl chloride plastic material and a preparation method thereof, and the polyvinyl chloride plastic material comprises the following components by weight: 100 parts of a polyvinyl chloride matrix; 5 to 10 parts of light response type nano particles with # imgabs 0 # as a core and # imgabs 1 # as a shell; 2-8 parts of a halogen ion carrier type mesoporous material; 1-5 parts of a halogen free radical trapping agent; and 1-3 parts of a layered barrier material. According to the technical scheme, the technical problems that in the prior art, a polyvinyl chloride material is prone to light aging in a marine environment, and micro-plastic pollution is generated are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polyvinyl chloride materials, and in particular to a polyvinyl chloride plastic material and a preparation method thereof. Background Art

[0002] Polyvinyl chloride plastic materials are widely used in the field of wires and cables due to their excellent mechanical properties, electrical insulation properties and flame retardant properties. Especially in the manufacture of cable sheaths and insulation materials, polyvinyl chloride plastic materials not only provide good mechanical protection and electrical insulation properties, but also have advantages such as good processing performance and moderate cost. With the rapid development of global power and communication infrastructure, the application scope of polyvinyl chloride cable materials continues to expand, and market demand continues to grow.

[0003] However, a large number of PVC cables are laid in marine environments such as marine engineering, cross-sea bridges, and offshore oil and gas platforms, and are exposed to strong ultraviolet radiation and salty seawater for a long time. This complex environment causes the PVC material to age faster, resulting in microcracks and peeling, which not only reduces the service life of the cable, but more seriously, the microplastic particles produced during the aging process will cause continuous pollution to the marine ecological environment. Especially under light conditions, the chloride ions in seawater will accelerate the degradation of the material. This synergistic effect poses severe challenges to the environmental adaptability of traditional PVC cable materials. Therefore, it is of great practical significance to develop a PVC plastic material that can resist light aging in the marine environment and reduce the production of microplastics. Summary of the invention

[0004] The main purpose of the present invention is to solve the technical problem that polyvinyl chloride materials existing in the prior art are prone to light aging in the marine environment and produce microplastic pollution.

[0005] The first aspect of the present invention provides a polyvinyl chloride plastic material, which comprises the following components by weight: 100 parts of polyvinyl chloride base; For the core, The invention comprises 5-10 parts of light-responsive nanoparticles as a shell; 2-8 parts of halogen ion carrier type mesoporous materials; 1-5 parts of halogen free radical scavengers; and 1-3 parts of layered barrier materials.

[0006] Optionally, the For the core, The light-responsive nanoparticles with a shell have the following characteristics: The core is anatase type, the particle size is 20-50nm, and the specific surface area is 80-120 / g; The shell is a porous structure with a shell thickness of 10-30nm and a pore size of 5-20nm; / The molar ratio is 0.5-2:1; The molar ratio is 0.1-0.5:1.

[0007] Optionally, the halogen ion carrier type mesoporous material comprises: the carrier material is selected from mesoporous silica or mesoporous alumina, the pore size is 2-10nm, the specific surface area is 300-600 / g; the surface of the carrier is modified by amino or carboxyl groups; the loaded halogen ion source is selected from one or more of lanthanum chloride, cerium chloride, and neodymium chloride, and the loading amount is 10-30% of the carrier mass.

[0008] Optionally, the halogen free radical scavenger is a cerium-based metal organic framework material having the following characteristics: a pore size of 1-3 nm; a specific surface area of ​​500-1000 m2 / g; and a coordination metal of ; The organic ligand is selected from one or more of terephthalic acid and 2,5-dihydroxyterephthalic acid.

[0009] Optionally, the layered barrier material has the following characteristics: the material is selected from one or more of hydrotalcite and layered double hydroxide; the aspect ratio is greater than 100; the sheet thickness is 1-5 nm; and the interlayer spacing is 0.8-1.5 nm.

[0010] Optionally, the mass ratio of each functional component satisfies: the mass ratio of photoresponsive nanoparticles to halogen ion carrier type mesoporous material is 1:0.2-1; the mass ratio of halogen ion carrier type mesoporous material to halogen free radical scavenger is 2-5:1; the mass ratio of halogen free radical scavenger to layered barrier material is 1:0.2-1.

[0011] A second aspect of the present invention provides a method for preparing a polyvinyl chloride plastic material, comprising: (1) Preparation of photoresponsive nanoparticles: Mix tetrabutyl titanate and hexadecyltrimethylammonium bromide, adjust the pH to 2-3, and stir; Hydrothermal reaction at 180-200℃ for 4-6h to obtain Precursor; Towards Add cerium nitrate solution and 30% hydrogen peroxide to the precursor dispersion and adjust the pH to 7-8; The reaction was carried out under 365 nm ultraviolet light for 2-4 h to obtain core-shell structured nanoparticles; (2) Preparation of halogen ion carrier type mesoporous materials: Under nitrogen protection, rare earth chloride solution was mixed with mesoporous material and stirred for 1 h; Add cerium-based metal organic framework material dissolved in N,N-dimethylformamide and stir at room temperature; Pulse ultrasound (power 400 W, intermittent ratio 1:1) was used for 30 min, allowed to stand for 2 h, and cycled three times; Centrifugation, washing, and drying to obtain a functionalized carrier; (3) Preparation of composite system: Ultrasonic dispersion of the products obtained in steps (1) and (2) in an ethanol-water mixed solution for 30 min; Add the layered barrier material and continue ultrasonic dispersion; The freeze (-20°C, 2 h)-thaw (25°C, 1 h) cycle was performed three times; Freeze drying to obtain functional composite powder; (4) Preparation of final material: blending the functional composite powder with the polyvinyl chloride body; Dry under vacuum at 60°C for 12 h; The target material was obtained by compounding using a twin-screw extruder.

[0012] Optionally, in step (1), the molar ratio of tetrabutyl titanate to hexadecyltrimethylammonium bromide is 1:1.5-2; the hydrothermal reaction pressure is 2-3 MPa; and the cerium nitrate and The molar ratio is 0.5-2:1; the UV power density is 10-20mW / .

[0013] Optionally, in steps (2) and (3): the concentration of rare earth chloride is 0.1-0.5 mol / L; the concentration of cerium-based metal organic framework material is 2-5 g / L; the volume ratio of ethanol-water mixed solution is 3:1; and the ultrasonic power density is 200-400 W / L.

[0014] Optionally, in step (4): the screw speed of the twin-screw extruder is 100-150rpm; the temperature of each section is: 150-160°C in the feeding zone, 160-165°C in the mixing zone, and 140-150°C in the discharging zone; the screw aspect ratio is 36:1; and the vacuum degree during the extrusion process is ≤-0.08MPa.

[0015] The technical solution provided by the embodiments of the present application has at least the following advantages: The present invention is designed to For the core, The core-shell photoresponsive nanoparticles achieve efficient absorption and energy conversion of ultraviolet light through the core-shell structure, significantly improving the light stability of the material. The core provides a photoresponsive active site. The shell passes through The reversible conversion of photogenerated carriers effectively regulates the transmission of photogenerated carriers, thereby inhibiting the photoaging process.

[0016] At the same time, the synergistic effect of halogen ion carrier mesoporous materials and halogen free radical scavengers was utilized to form a unique free radical regulation system in the seawater environment. The mesoporous materials can controllably release halogen ions and cooperate with the scavengers to effectively prevent the attack of chlorine free radicals on the polyvinyl chloride matrix, greatly reducing the degradation rate of the material.

[0017] In addition, a physical protection barrier was constructed using layered barrier materials. Their high aspect ratio and regular interlayer structure not only enhanced the mechanical properties of the material, but also significantly improved the material's water and oxygen barriers, further delaying the erosion of the seawater environment on the material. DETAILED DESCRIPTION

[0018] In order to make the technical means, creative features, purpose and efficacy of the present invention easy to understand, the present invention is further explained in conjunction with specific embodiments below, but the following embodiments are only preferred embodiments of the present invention, not all. Based on the embodiments in the implementation mode, other embodiments obtained by those skilled in the art without creative work all belong to the protection scope of the present invention. In the following embodiments, unless otherwise specified, the operating methods used are conventional operating methods, the equipment used are conventional equipment, and the equipment materials used in each embodiment are the same.

[0019] The raw materials used in the following examples are all commercially available products and do not require further purification before use. Among them, polyvinyl chloride substrate (SG-5, K value 67) was purchased from Sinopec Qilu Branch; tetrabutyl titanate (analytical grade, purity ≥ 98%) was purchased from Shanghai McLean Biochemical Technology Co., Ltd.; cerium nitrate hexahydrate (analytical grade, purity ≥ 99%) and lanthanum chloride, cerium chloride, and neodymium chloride (all analytical grade, purity ≥ 99%) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; hexadecyl trimethylammonium bromide (analytical grade, purity ≥ 99%) was purchased from Tianjin Komiou Chemical Reagent Co., Ltd.; mesoporous silica (MCM-41 type, specific surface area 450±50 / g) and mesoporous alumina (γ- , specific surface area 280±30 / g) was purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd.; terephthalic acid and 2,5-dihydroxyterephthalic acid (both analytical grade, purity ≥99%) were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; hydrotalcite ( , purity ≥95%) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. The twin-screw extruder (TEK-30A) was purchased from Nanjing Keya Chemical Equipment Co., Ltd., with a screw diameter of 30 mm and an aspect ratio of 36:1; the freeze dryer (FD-1C-80) was purchased from Shanghai Ailang Instrument Co., Ltd.

[0020] In the present invention, the morphology and particle size distribution of the nanoparticles were observed using a field emission scanning electron microscope (FEI Quanta 450FEG); the specific surface area and pore size distribution were measured using a nitrogen adsorption-desorption method (Micromeritics ASAP 2460); and the crystal structure was characterized by an X-ray diffractometer (Bruker D8 Advance); In the shell The ratio was determined by X-ray photoelectron spectroscopy (Thermo ESCALAB 250Xi); the light aging performance of the material was evaluated by a xenon lamp aging test chamber (Shanghai Xinjia ESP-100) with a light intensity of 550W / , wavelength range is 280-800nm, test temperature is 45±2℃, relative humidity is 50±5%. The aging test is carried out in a cycle of "illumination 8h-condensation 4h", the test sample size is 100mm×10mm×4mm, and it is conditioned for 24h in a standard environment of 23±2℃ and relative humidity 50±5% before the test; the amount of microplastics produced is determined by filtration-microscope observation method, using nylon membrane (pore size 0.45μm) for filtration and optical microscope (OlympusBX53) for observation and counting; the mechanical properties of the material are tested according to GB / T 1040.1-2006 standard.

[0021] This paper focuses on the photoaging problem of polyvinyl chloride (PVC) materials in marine environments and studies the aging mechanism mediated by halogen free radicals. - ) will generate active halogen free radicals under ultraviolet light These free radicals have strong selective oxidation ability and can attack the C-H and C-C bonds in the PVC molecular chain, causing material degradation. At the same time, light also produces hydroxyl radicals (•OH), which synergize with halogen free radicals to accelerate the degradation process of PVC.

[0022] Based on the above mechanism, the present invention designs a multi-cooperative protection system. First, For the core, The light-responsive nanoparticles with shells play a key role in this system: The core can effectively absorb ultraviolet light, and Shell through The reversible conversion process captures photogenerated electrons and blocks the generation pathway of photoinduced free radicals. The porous structure of the shell provides a large number of active sites, which significantly improves the electron capture efficiency.

[0023] Halogen ion carrier-type mesoporous materials and halogen free radical scavengers form the second line of defense. The mesoporous carrier is loaded with rare earth chloride after surface modification, and can release Cl in a controllable manner under pH response conditions. - , reducing the local Cl - concentration, inhibiting the generation of halogen free radicals. At the same time, cerium-based metal organic framework materials, as free radical scavengers, have unique pore structures (1-3nm) and unsaturated coordination. The sites can efficiently capture the generated halogen free radicals and block the degradation chain reaction.

[0024] Layered composite barrier materials build the third protective barrier. Hydrotalcite or layered double hydroxide has a unique layered structure. Its high aspect ratio (>100) and regular interlayer spacing (0.8-1.5nm) can not only block the penetration of seawater and oxygen, but also adsorb and fix free radicals, further improving the stability of the material.

[0025] The above triple protection system forms a synergistic protection network through precise ratio design. The mass ratio of light-responsive nanoparticles to halogen ion carriers is controlled in the range of 1:0.2-1, ensuring the balance between light protection and ion regulation; the mass ratio of halogen ion carriers to free radical scavengers is 2-5:1, optimizing the synergistic effect of ion release and free radical capture; the mass ratio of free radical scavengers to layered barrier materials is 1:0.2-1, achieving the best combination of chemical protection and physical barriers.

[0026] Preparation and characterization of photoresponsive nanoparticles: The present invention adopts a hydrothermal method combined with an in-situ growth strategy to prepare core-shell structured nanoparticles. First, the hydrothermal method can be used to control the preparation of anatase-type nanoparticles with specific crystal faces. The core is then subjected to UV-assisted in situ redox reactions. Surface growth porous Shell. Among them, hexadecyl trimethyl ammonium bromide is used as a morphology regulator, which not only controls The crystal face growth is also The shell layer provides a template for the porous structure; the addition of hydrogen peroxide promotes Controlled oxidation is conducive to the formation of stable Proportion.

[0027] During the preparation process, pH value is a key process parameter. During the core preparation stage, the pH value is controlled in the range of 2-3, which is conducive to the formation of anatase phase and obtaining a higher crystallinity. When the shell grows, the pH value needs to be adjusted to 7-8. The oxidation rate is moderate, which is conducive to the formation of a uniform porous structure. In terms of hydrothermal reaction conditions, the temperature is controlled in the range of 180-200°C, the pressure is maintained at 2-3MPa, and the reaction time is 4-6h. The nucleus growth rate is moderate, which is conducive to the formation of uniform particles of 20-50nm. When the shell layer is subsequently grown under illumination conditions, 365nm ultraviolet light is used and the power density is controlled at 10-20mW / In the range of 2-4 hours, the irradiation time is 2-4 hours. Directed growth and forming an ideal Proportion.

[0028] The prepared products were observed by field emission scanning electron microscopy, and the results showed that the core-shell structured nanoparticles were regular spherical. The average core particle size is 35nm. The shell thickness is about 20nm, and the surface shows obvious porous characteristics. X-ray diffraction results show that The core is a pure anatase phase with characteristic peaks at 25.3°, 37.8°, and 48.0°; The shell layer presents a typical fluorite structure, with characteristic peaks located at 28.5°, 33.1°, and 47.5°. Nitrogen adsorption-desorption tests show that the specific surface area of ​​core-shell nanoparticles reaches 95 / g, the pore size is mainly distributed in the range of 5-20nm. X-ray photoelectron spectroscopy test shows that In the shell The molar ratio is 0.3:1, which is in the optimal activity range.

[0029] Preparation and characterization of halogen ion carriers: The present invention adopts a surface modification combined with an impregnation method to prepare a halogen ion carrier type mesoporous material. The technical key points of the preparation method are: mesoporous silica or mesoporous alumina is selected as a basic carrier, surface amino or carboxyl modification is first performed, and then the loading of rare earth chloride is achieved through controlled impregnation. Surface modification not only provides a stable functional group, but also realizes the controlled release of halogen ions; the selection of rare earth chloride as a halogen ion source utilizes the strong coordination effect between rare earth ions and surface groups, thereby ensuring the stability of the loading.

[0030] In the specific preparation process, the mesoporous carrier material is first vacuum activated at 250°C for 4 hours to remove moisture and impurities adsorbed on the surface. Then, under nitrogen protection, the carrier surface is modified with 3-aminopropyltriethoxysilane or carboxylsilane, the modification temperature is controlled at 80-90°C, and the reaction time is 6 hours. The modified carrier is filtered, washed, and vacuum dried at 60°C for 12 hours. The surface-modified carrier is immersed in a rare earth chloride solution, the solution concentration is controlled in the range of 0.1-0.5 mol / L, and stirred at room temperature for 1 hour, during which nitrogen protection is maintained.

[0031] The prepared halogen ion carrier material was characterized: the nitrogen adsorption-desorption test results showed that the material maintained a good mesoporous structure with a specific surface area of ​​450 / g or more, and the main pore size distribution is in the range of 2-10nm. Fourier transform infrared spectroscopy analysis confirmed that the surface of the carrier was successfully grafted with amino or carboxyl groups, with characteristic peaks located at 1560cm-1 and 1650cm-1. Thermogravimetric analysis showed that the actual loading amount of rare earth chloride reached 25% of the carrier mass, and it had good thermal stability below 150°C.

[0032] The material showed an ideal pH response performance in a simulated seawater environment (pH=8.2) as measured by inductively coupled plasma emission spectroscopy, and the cumulative release of halogen ions within 24 hours did not exceed 15% of the total loading, showing good controlled release characteristics. Scanning electron microscopy and transmission electron microscopy observations showed that the surface morphology and pore structure of the loaded material remained intact, with no obvious agglomeration, which is of great significance for maintaining the dispersion and function of the material.

[0033] Preparation and characterization of halogen free radical scavengers: The present invention selects cerium-based metal organic framework materials as halogen free radical scavengers and adopts a solvothermal method to prepare them. The key to the method is to use hexahydrated cerium nitrate as a metal source, terephthalic acid or 2,5-dihydroxyterephthalic acid as an organic ligand, and to construct a metal organic framework material with a specific pore structure by regulating the crystallization process in an N,N-dimethylformamide solvent. The coordination unsaturation nature and spatial configuration of organic ligands play a decisive role in the free radical capture performance of the material.

[0034] In the preparation process, cerium nitrate hexahydrate and organic ligand are first dissolved in N,N-dimethylformamide at a molar ratio of 1:1.5, and ultrasonic dispersion is performed for 30 minutes to fully dissolve them. The mixed solution is transferred to a polytetrafluoroethylene-lined reactor and crystallized at 120°C for 48 hours. The product is centrifuged, washed three times with N,N-dimethylformamide and anhydrous ethanol in sequence, and finally vacuum dried at 60°C for 12 hours to obtain a light yellow powder product.

[0035] X-ray diffraction analysis of the prepared cerium-based metal organic framework material showed that characteristic diffraction peaks appeared at diffraction angles of 7.5°, 10.2° and 12.8°, confirming that the material has a regular crystal structure. Nitrogen adsorption-desorption test showed that the specific surface area of ​​the material reached 850 / g, pore size distribution is concentrated in the range of 1-3nm, which is a typical microporous structure. Thermogravimetric analysis shows that the material has good thermal stability below 300℃, which meets the needs of practical applications.

[0036] X-ray photoelectron spectroscopy analysis showed that the It is in a coordination unsaturated state, which is conducive to the capture of halogen free radicals. Through electron spin resonance spectroscopy testing, under simulated light aging conditions, the material showed excellent capture ability for halogen free radicals, and more than 90% of halogen free radicals can be captured within 5 minutes. Fourier transform infrared spectroscopy analysis shows that the free radical capture process will not destroy the skeleton structure of the material, ensuring its long-term stability.

[0037] Preparation and characterization of layered barrier materials: The present invention selects hydrotalcite or layered double hydroxide as the layered barrier material and adopts a coprecipitation method combined with hydrothermal treatment to prepare it. The technical key point of the method is to obtain a layered structure with a high aspect ratio and uniform interlayer spacing by controlling the precipitation rate and crystallization conditions of the metal salt. The layered structure and sheet size of the material have a decisive influence on its barrier performance and dispersibility.

[0038] In the specific preparation process, taking the preparation of magnesium aluminum hydrotalcite as an example, magnesium nitrate and aluminum nitrate are dissolved in deionized water at a molar ratio of 3:1 to prepare a mixed solution with a total metal ion concentration of 1.0 mol / L. A mixed alkali solution of sodium carbonate and sodium hydroxide is also prepared. Under nitrogen protection, the mixed metal salt solution and the alkali solution are simultaneously added dropwise to a reactor filled with deionized water at a constant rate, and the pH value of the reaction system is controlled at 10.0±0.2. After precipitation is completed, the slurry is transferred to a hydrothermal reactor and treated at 140°C for 24 hours. The product is centrifuged, washed to neutrality, and dried by freeze-drying technology to obtain a white powder product.

[0039] The prepared layered material was characterized, and X-ray diffraction analysis showed that the product had typical layered structural characteristic diffraction peaks, indicating that a regular layered structure was formed. Through transmission electron microscopy, the material showed a lamellar morphology, with a single layer thickness of about 2nm, a lateral size of about 500nm, and an aspect ratio of 250. Atomic force microscopy testing further confirmed the lamellar structure of the material, and the surface roughness was controlled within 0.5nm.

[0040] Through small-angle X-ray scattering analysis, the interlayer spacing of the layered material is stable at 1.2nm. This suitable interlayer spacing is conducive to the uniform dispersion of the material in the polymer matrix and can effectively block the penetration of water and oxygen. Thermogravimetric analysis shows that the material has good thermal stability below 400°C and meets the requirements of subsequent processing. Using a water vapor transmission rate tester, the material has a barrier rate of 85% for water vapor and 90% for oxygen, showing excellent barrier properties.

[0041] Example 1 Prepare the polyvinyl chloride plastic material as follows: (1) The following raw materials are measured by weight: 100 parts of polyvinyl chloride substrate; 7 parts of light-responsive nanoparticles; 5 parts of halogen ion carrier; 2 parts of free radical scavenger; and 2 parts of layered barrier material.

[0042] (2) Preparation of light-responsive nanoparticles: 2.72 g of tetrabutyl titanate and 0.58 g of hexadecyltrimethylammonium bromide were mixed, 50 mL of anhydrous ethanol was added, the pH was adjusted to 2.5, and stirred for 30 minutes. The mixture was transferred to a hydrothermal reactor and reacted at 190°C for 5 hours. The precursor was dispersed in 100 mL of deionized water, and 4.34 g of cerium nitrate solution (0.5 mol / L) was slowly added, and 5 mL of 30% hydrogen peroxide was added at the same time, and the pH was adjusted to 7.5. The reaction was carried out under 365 nm ultraviolet light (15 mW / cm2) for 3 hours, and then centrifuged, washed, and dried at 60 ° C to obtain core-shell structured nanoparticles.

[0043] (3) Preparation of halogen ion carrier: 5 g of mesoporous silica was vacuum activated at 250 °C for 4 hours, and then 100 mL of anhydrous toluene and 3 mL of 3-aminopropyltriethoxysilane were added, and refluxed at 85 °C for 6 hours. After the product was filtered and washed, 50 mL of cerium chloride solution (0.3 mol / L) was added, and stirred at room temperature for 1 hour under nitrogen protection. Pulse ultrasonic treatment was performed at 400 W power and intermittent ratio of 1:1 for 30 minutes, and then allowed to stand for 2 hours, and the cycle was repeated 3 times. The functionalized carrier was obtained by centrifugation, washing, and drying.

[0044] (4) Preparation of functional composite system: The materials obtained in steps (2) and (3) were ultrasonically dispersed in 75 mL of ethanol-water mixed solution (volume ratio 3:1) for 30 minutes, hydrotalcite was added, and ultrasonication was continued for 30 minutes. Freeze (-20°C, 2h)-thaw (25°C, 1h) cycles were performed 3 times, and functional composite powder was obtained by freeze drying.

[0045] (5) Final material preparation: The functional composite powder and the polyvinyl chloride matrix were mixed according to the ratio and vacuum dried at 60°C for 12 hours. The composite was made by a twin-screw extruder with a screw speed of 120 rpm, a feed zone of 155°C, a mixing zone of 162°C, and a discharge zone of 145°C. The vacuum degree was maintained at -0.09 MPa during the extrusion process.

[0046] Example 2 Prepare the polyvinyl chloride plastic material as follows: (1) The following raw materials are measured by weight: 100 parts of polyvinyl chloride substrate; 8 parts of light-responsive nanoparticles; 4 parts of halogen ion carrier; 3 parts of free radical scavenger; and 1.5 parts of layered barrier material.

[0047] (2) The remaining steps are the same as in Example 1.

[0048] Example 3 Prepare the polyvinyl chloride plastic material as follows: (1) The following raw materials are measured by weight: 100 parts of polyvinyl chloride substrate; 6 parts of light-responsive nanoparticles; 6 parts of halogen ion carrier; 2 parts of free radical scavenger; and 2.5 parts of layered barrier material.

[0049] (2) The remaining steps are the same as in Example 1.

[0050] Comparative Example 1 Only polyvinyl chloride matrix was used without adding other functional components, and the material was prepared according to the extrusion conditions of Example 1.

[0051] Comparative Example 2 Follow these steps to prepare the materials: (1) Measure the raw materials by weight: 100 parts of polyvinyl chloride matrix; 7 parts of light-responsive nanoparticles.

[0052] (2) The remaining steps are the same as in Example 1.

[0053] Test results: The performance test results of different embodiments and comparative examples are shown in the following table The results show that: 1. Anti-light aging performance: After 500 hours of xenon lamp accelerated aging, the tensile strength retention rate of the materials prepared in Examples 1-3 of the present invention all reached more than 88%, which is much higher than 45% of Comparative Example 1 and 60% of Comparative Example 2. This shows that the multiple protection system designed by the present invention can effectively inhibit the light aging process. Among them, Example 1 performed best, with a tensile strength retention rate of 92%, which was mainly due to the optimal ratio of 7:5 of light-responsive nanoparticles and halogen ion carriers, achieving the synergistic effect of light protection and free radical regulation.

[0054] 2. Microplastic generation: Through surface analysis of the material after 500 hours of aging, the microplastic reduction rate of Examples 1-3 all reached more than 80%, among which Example 1 had the most significant effect, with a reduction rate of 85%. In contrast, in Comparative Example 2, the microplastic reduction rate was only 35% by adding only light-responsive nanoparticles. This shows that the synergistic effect of the layered barrier material designed by the present invention and the free radical capture system plays an important role in inhibiting the surface peeling of the material and the formation of microcracks.

[0055] 3. Material oxidation degree: From the perspective of carbonyl index growth rate, the oxidation degree of Examples 1-3 is significantly lower than that of the comparative example. The carbonyl index growth rate of Example 1 is only 22%, while that of Comparative Example 1 and Comparative Example 2 is 100% and 75%, respectively. This shows that the multi-protection system of the present invention can effectively block the oxidative degradation process, in which the role of the halogen free radical scavenger is particularly critical.

[0056] 4. Barrier performance: The water vapor permeability of Examples 1-3 is significantly lower than that of the comparative example, among which Example 1 is only 0.52 g / m2·24h, which is 78% lower than that of the comparative example 1. This is mainly due to the "maze effect" formed by the layered barrier material in the system, which effectively prolongs the permeation path of water molecules.

[0057] 5. Comprehensive performance analysis: The surface morphology of the samples after aging for 500 hours was observed by scanning electron microscopy. The surfaces of Examples 1-3 were smooth without obvious cracks and holes, while a large number of microcracks and peeling appeared on the surfaces of Comparative Examples 1 and 2. This further confirms the synergistic effect of the multiple protection system designed in the present invention in inhibiting material aging and degradation. In addition, the introduction of the functional components in the examples did not affect the transparency and processing performance of the materials, and the product appearance and mechanical properties met the actual application requirements.

[0058] 6. Mechanism analysis: Combined with the electron spin resonance spectroscopy test results, the free radical signal intensity observed in Example 1 is only 15% of that in Comparative Example 1, which indicates that the protection system designed by the present invention can inhibit the generation of free radicals from the source and effectively capture the generated free radicals through multiple action mechanisms, thereby achieving all-round protection of the material.

[0059] The above results fully prove that the present invention has successfully solved the problem of light aging of polyvinyl chloride materials in the marine environment through the design of a multiple synergistic protection system, significantly reduced the generation of microplastics, and provided a new technical solution for the development of polyvinyl chloride materials for marine engineering.

[0060] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A polyvinyl chloride plastic material, characterized in that: The polyvinyl chloride plastic material comprises the following components by weight: 100 parts of polyvinyl chloride base; For the core, The invention comprises 5-10 parts of light-responsive nanoparticles as a shell; 2-8 parts of halogen ion carrier type mesoporous materials; 1-5 parts of halogen free radical scavengers; and 1-3 parts of layered barrier materials.

2. The polyvinyl chloride plastic material according to claim 1, characterized in that: Said For the core, The light-responsive nanoparticles with a shell have the following characteristics: The core is anatase type, the particle size is 20-50nm, and the specific surface area is 80-120 / g; The shell is a porous structure with a shell thickness of 10-30nm and a pore size of 5-20nm; / The molar ratio is 0.5-2:1; The molar ratio is 0.1-0.5:

1.

3. The polyvinyl chloride plastic material according to claim 1, characterized in that: The halogen ion carrier type mesoporous material comprises: the carrier material is selected from mesoporous silica or mesoporous alumina, the pore size is 2-10nm, the specific surface area is 300-600 / g; the surface of the carrier is modified by amino or carboxyl groups; the loaded halogen ion source is selected from one or more of lanthanum chloride, cerium chloride, and neodymium chloride, and the loading amount is 10-30% of the carrier mass.

4. The polyvinyl chloride plastic material according to claim 1, characterized in that: The halogen free radical scavenger is a cerium-based metal organic framework material, having the following characteristics: The pore size is 1-3nm; the specific surface area is 500-1000m2 / g; the coordination metal is ; The organic ligand is selected from one or more of terephthalic acid and 2,5-dihydroxyterephthalic acid.

5. The polyvinyl chloride plastic material according to claim 1, characterized in that: The layered barrier material has the following characteristics: the material is selected from one or more of hydrotalcite and layered double hydroxide; the aspect ratio is greater than 100; the sheet thickness is 1-5 nm; and the interlayer spacing is 0.8-1.5 nm.

6. The polyvinyl chloride plastic material according to any one of claims 1 to 5, characterized in that: The mass ratio of each functional component satisfies: the mass ratio of photoresponsive nanoparticles to halogen ion carrier type mesoporous material is 1:0.2-1; the mass ratio of halogen ion carrier type mesoporous material to halogen free radical scavenger is 2-5:1; the mass ratio of halogen free radical scavenger to layered barrier material is 1:0.2-1.

7. A method for preparing a polyvinyl chloride plastic material, used for preparing the polyvinyl chloride plastic material according to any one of claims 1 to 6, characterized in that: The preparation method of the polyvinyl chloride plastic material comprises: (1) Preparation of photoresponsive nanoparticles: Mix tetrabutyl titanate and hexadecyltrimethylammonium bromide, adjust the pH to 2-3, and stir; Hydrothermal reaction at 180-200℃ for 4-6h to obtain Precursor; Towards Add cerium nitrate solution and 30% hydrogen peroxide to the precursor dispersion and adjust the pH to 7-8; The reaction was carried out under 365 nm ultraviolet light for 2-4 h to obtain core-shell structured nanoparticles; (2) Preparation of halogen ion carrier type mesoporous materials: Under nitrogen protection, rare earth chloride solution was mixed with mesoporous material and stirred for 1 h; Add cerium-based metal organic framework material dissolved in N,N-dimethylformamide and stir at room temperature; Pulse ultrasound (power 400 W, intermittent ratio 1:1) was used for 30 min, allowed to stand for 2 h, and cycled three times; Centrifuging, washing and drying to obtain a functionalized carrier; (3) Preparation of composite system: Ultrasonic dispersion of the products obtained in steps (1) and (2) in an ethanol-water mixed solution for 30 min; Add the layered barrier material and continue ultrasonic dispersion; Freeze (-20°C, 2h)-thaw (25°C, 1h) for 3 cycles; Freeze drying to obtain functional composite powder; (4) Preparation of final material: blending the functional composite powder with the polyvinyl chloride body; Dry under vacuum at 60°C for 12 h; The target material was obtained by compounding using a twin-screw extruder.

8. The method for preparing polyvinyl chloride plastic material according to claim 7, characterized in that: In step (1), the molar ratio of tetrabutyl titanate to hexadecyltrimethylammonium bromide is 1:1.5-2; the hydrothermal reaction pressure is 2-3 MPa; cerium nitrate and The molar ratio is 0.5-2:1; the UV power density is 10-20mW / .

9. The method for preparing a polyvinyl chloride plastic material according to claim 7, characterized in that: In steps (2) and (3): the concentration of rare earth chloride is 0.1-0.5 mol / L; the concentration of cerium-based metal organic framework material is 2-5 g / L; the volume ratio of ethanol-water mixed solution is 3:1; and the ultrasonic power density is 200-400 W / L.

10. The method for preparing polyvinyl chloride plastic material according to claim 7, characterized in that: In step (4), the screw speed of the twin-screw extruder is 100-150 rpm; the temperature of each section is: 150-160° C. in the feeding zone, 160-165° C. in the mixing zone, and 140-150° C. in the discharging zone; the screw aspect ratio is 36:1; and the vacuum degree during the extrusion process is ≤-0.08 MPa.

Citation Information

Patent Citations

  • Metal organic frame material-based composite heat stabilizer for PVC (polyvinyl chloride) and application of metal organic frame material-based composite heat stabilizer

    CN104387702A

  • Polypropylene film, preparation method thereof, aluminum-plastic film and lithium battery

    CN110527450A

  • Ce-based organic metal complex catalytic material and preparation method and application thereof

    CN111450894A

  • Preparation method of flame-retardant anti-aging micro-foaming PVC composite material

    CN116041771A

  • Preparation method of ultraviolet shielding additive based on MOF material

    CN118185048A

Cited By

  • Environment-friendly PVC-U plastic pipe fitting and manufacturing method thereof

    CN120307709A